PENGENALAN DASAR-DASAR SISTEM PAKAR - Landung Sudarmana (Jurnal Teknomatika, 2010)
An expert system is a system that employs human knowledge captured in a computer to solve problems that ordinarily require human expertise. Well- designed systems imitate the reasoning processes experts use to solve specific problems. Such systems can be used by nonexperts to improve their problem- solving capabilities. Expert systems (ES) can also be used by experts as knowledgeable assistants. ES are used to propagate scare knowlegde resource for improved, consistent result. Ultimately, such could function better than any single human expert in making judgments in a specific, usually narrow, area of expertise. This possibility may have a significant impact both on advisory professionals and on organization and management.